2014
DOI: 10.1128/mbio.01690-14
|View full text |Cite
|
Sign up to set email alerts
|

Streptolysin O and NAD-Glycohydrolase Prevent Phagolysosome Acidification and Promote Group A Streptococcus Survival in Macrophages

Abstract: Group A Streptococcus (GAS, Streptococcus pyogenes) is an ongoing threat to human health as the agent of streptococcal pharyngitis, skin and soft tissue infections, and life-threatening conditions such as necrotizing fasciitis and streptococcal toxic shock syndrome. In animal models of infection, macrophages have been shown to contribute to host defense against GAS infection. However, as GAS can resist killing by macrophages in vitro and induce macrophage cell death, it has been suggested that GAS intracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
107
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(136 citation statements)
references
References 45 publications
9
107
0
2
Order By: Relevance
“…Studies in the recent decade demonstrate SPN and SLO play important roles in circumventing the host immune system via i) inhibiting group A Streptococcus internalization by host cells, 3 ii) promoting apoptosis of macrophages, 29 iii) preventing the bactericidal effects of neutrophils, 7,8 iv) disrupting maturation of the phagosome, and v) promoting intracellular bacterial survival. 5,6,30 Recent advances in S. pyogenes population genomics and pathogenesis further underlined the important roles of SPN and SLO in virulence. We previously showed that polymorphisms in the nga upstream region result in enhanced production of SPN and SLO, which is strongly associated with increased transmission and virulence of epidemic M1 and M89 clones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in the recent decade demonstrate SPN and SLO play important roles in circumventing the host immune system via i) inhibiting group A Streptococcus internalization by host cells, 3 ii) promoting apoptosis of macrophages, 29 iii) preventing the bactericidal effects of neutrophils, 7,8 iv) disrupting maturation of the phagosome, and v) promoting intracellular bacterial survival. 5,6,30 Recent advances in S. pyogenes population genomics and pathogenesis further underlined the important roles of SPN and SLO in virulence. We previously showed that polymorphisms in the nga upstream region result in enhanced production of SPN and SLO, which is strongly associated with increased transmission and virulence of epidemic M1 and M89 clones.…”
Section: Discussionmentioning
confidence: 99%
“…2e4 SLO is a cholesteroldependent cytolysin that forms pores in host cell membranes. SPN and SLO inhibit phagocytosis, 3 inhibit maturation of autophagosomes, 5,6 impair neutrophil oxidative burst, 7 and prevent the killing of S. pyogenes by a variety of host immune cells. 3,5e8 SPN and SLO are interconnected in many ways.…”
mentioning
confidence: 99%
“…In addition, Mga in M59 GAS influences the expression of an operon encoding streptolysin O (SLO) and NAD-glycohydrolase (NADase) and its intracellular inhibitor immunity factor for Streptococcus pyogenes NADase (IFS). Both SLO and NADase are proven virulence factors and have been implicated in intracellular survival and GAS resistance to macrophage-mediated cytotoxicity (48)(49)(50)(51)(52). Beyond the core regulon, genes regulated by Mga in the two serotypes diverge significantly and point toward differing metabolic capabilities of the two serotypes.…”
Section: Discussionmentioning
confidence: 99%
“…S. pyogenes expresses a large arsenal of virulence factors (1, 2), many of which are well studied. These include antiphagocytic hyaluronic acid capsule (3), the cytotoxins S. pyogenes NADase (SPN) and streptolysin O (SLO) (4,5), and a potent extracellular cysteine protease, SpeB (6,7). These virulence factors are regulated by the CovR/CovS two-component regulatory system (8)(9)(10).…”
mentioning
confidence: 99%